A Behavioral Intervention for Reducing Postcompletion Errors in a Safety-Critical System. (September 2015) - McDonald, Joseph D.; Durso, Francis T.
Objective: We investigated the effectiveness of a theoretically motivated intervention at reducing procedural errors in train yard operations, where making these errors could be costly or life-threatening. Background: A widespread and persistent memory error that people commit on a daily basis is the postcompletion error (PCE), that is, forgetting to complete the final step of a procedural task in which the final step occurs after completion of the task goal. PCEs occur in the railroad industry when a locomotive conductor changes the direction of a rail switch but fails to report this change. This particular error could contribute to unsafe conditions as another train traveling on the same track could derail. Although training can help reduce some of the factors leading to unsafe conditions on the rail, research has demonstrated that PCEs are different from other errors of omission in that they cannot be eliminated through training, which makes them a difficult problem to address. Method: Twenty-eight undergraduates completed train yard tasks within a mid-fidelity simulator used in commercial rail operations for training. Each participant received the behavioral intervention in one block and no intervention in another. Specifically, participants were required to perform an additional task designed to remind participants of the postcompletion step. Results: Our intervention significantly reduced PCE rates in the context of train yard operations, on average by 65%. Conclusion: We discuss implications of the effectiveness of our intervention at reducing train yard accidents and how this outcome can contribute to the literature on the cause of PCEs. Application: In cases such as the railroad industry, where redesigning technology is prohibitive, our behavioral intervention is an effective alternative for significantly reducing PCEs.